Pengaruh Kekurangan Air Terhadap Transportasi Hara Pada Tanaman Padi - Charles Septiawan Zebua; Nurul Hamidah Dohona; Andi Donal Zebua; Apriani Hia; Ariel Nezer Perlindungan Halawa; Basri Calvianus Waruwu; Helmin Parida Zebua (CV. SINAR HOWUHOWU, 2026)
Water deficiency is one of the major abiotic factors that significantly affects the growth and productivity of rice (Oryza sativa L.). Insufficient water availability disrupts vital physiological processes such as nutrient absorption, translocation, and distribution from roots to plant tissues. This study aims to analyze the effects of water shortage on the nutrient transport mechanism in rice plants. The methods included observations of soil moisture content, leaf nutrient levels, and transpiration rates under various drought treatments. The results revealed that water deficiency significantly reduced the roots’ ability to absorb essential macronutrients such as nitrogen (N), phosphorus (P), and potassium (K), due to decreased mass flow and ion diffusion in the soil. Furthermore, the reduction in turgor pressure and xylem activity disturbance inhibited the upward transport of nutrients, leading to lower vegetative growth and yield. Overall, this study emphasizes that optimal water availability is a key factor in maintaining nutrient transport efficiency and rice productivity, providing a scientific basis for developing adaptive irrigation strategies under drought conditions.